Responding to uncertain conditions : new research on strategic adaptation - Andersen, Torben Juul (Emerald studies in global strategic responsiveness., 2023)
A number of truly disruptive events have occurred in recent times, from the financial crisis and the pandemic to political conflict with broad ramifications for international business conduct. National borders have been severely constrained with radical effects on global value-chains and supply conditions. We must respond to these unpredictable developments in ways that create resilience and advance sustainable solutions. The global business environment is highly uncertain, fractured by unforeseen events and making decisions that deal with a largely unknown future. Following the global scale of COVID-19, the divergent uncoordinated actions of regimes around the world, and the more recent demonstration of brutal military interventions in Ukraine, the long-term belief that globalization is the bedrock of future wealth-creation is being questioned. As the system scrambles to cope with the costs of necessary adjustments to realign the international economic system, we realize that organizations must improve their ability to respond. To support these considerations and foster constructive thinking about effective response capabilities, this volume of articles presents a new set of studies that attempt to better understand and address this very need. The contributions consider the diverse effects of institutional settings and subtle organizational strategy-making contexts gauging ways to gain flexibility and strategic adaptability that can generate sustainable performance outcomes.